PROBLEMS OF PROVIDING METHODOLOGICAL SUPPORT FOR FORENSIC CONSTRUCTION EXAMINATIONS IN ARBITRATION PROCEEDINGS - E. Stativa (Теория и практика судебной экспертизы)
The problems of building the methodological apparatus of forensic construction examinations in arbitration proceedings are de!ned; the objective and subjective nature of these problems is expounded, and some solutions are briefly outlined.